2022
DOI: 10.3145/epi.2022.mar.13
|View full text |Cite
|
Sign up to set email alerts
|

Promoción de la lectura en la sociedad digital. El book-trailer del libro ilustrado de no ficción como epitexto virtual en la definición de un nuevo discurso

Abstract: Within the framework of the information society, we are witnessing a paradigm shift in reading characterized by the convergence of analog and digital supports and the consequent challenges. In this context, the illustrated nonfiction book emerges as a format with great editorial vitality. They are open works subject to the reader’s critical interpretation that move away from the traditional encyclopedic discourse and towards a confluence between art and knowledge. As a way of promoting these books, the book-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
11

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 29 publications
3
11
0
11
Order By: Relevance
“…In summary, virtual epitexts for the promotion of children's picturebooks may provide mediators and readers with means, such as those revealed in the selection above, with which to develop the basis of critical thinking and meet, in this way, the challenge posed by the digital society in training readers within the framework of a biliteracy that has already been established (Wolf, 2018). Following on from previous studies (Tabernero-Sala et al, 2022), the selected virtual epitexts present discourse markers typical of the promotion of the non-fiction picturebook, thereby confirming,…”
Section: The Multimodal Discoursesupporting
confidence: 74%
See 1 more Smart Citation
“…In summary, virtual epitexts for the promotion of children's picturebooks may provide mediators and readers with means, such as those revealed in the selection above, with which to develop the basis of critical thinking and meet, in this way, the challenge posed by the digital society in training readers within the framework of a biliteracy that has already been established (Wolf, 2018). Following on from previous studies (Tabernero-Sala et al, 2022), the selected virtual epitexts present discourse markers typical of the promotion of the non-fiction picturebook, thereby confirming,…”
Section: The Multimodal Discoursesupporting
confidence: 74%
“…We decided to analyze how publishers developed digital promotion of children's picturebooks at that time, since, as shown in Figure 1, the number of publications on YouTube and Vimeo in 2020 increased. As for the promotion methods, we confirmed that the main, most stable method, which acted as content repository, was YouTube (Tabernero-Sala et al, 2022), and, to a lesser extent, Vimeo. Furthermore, publishers generally ran promotion on different social media, such as Instagram or Facebook, due to the immediate nature of these media and their great capacity for dissemination.…”
Section: Methodssupporting
confidence: 57%
“…Los resultados aportados nos conducen a afirmar la validez de implementar el LINF para promover el desarrollo del pensamiento crítico en el alumnado de EP y, en consecuencia, contribuir a los constantes desafíos comunicativos que emergen del nuevo ecosistema digital en el que se desenvuelve el alumnado (Tabernero et al, 2022).…”
Section: Discusiones Y Conclusiónunclassified
“…Estos procesos formativos han permitido acercarse a los LINF, que, si bien son herederos de la corriente racionalista del siglo XIX, han proliferado tan vertiginosamente en el marco editorial que es preciso dotar a los docentes de elementos para acercarse críticamente a estos y determinar si son válidos o no para su utilización en el aula (Lartitegui, 2018). Por ello, en los últimos tres años han aflorado investigaciones muy útiles para el profesorado, bien porque se acercan a obras concretas y las analizan con detalle (Colón, 2021;Sampériz, Hernández et al, 2020;Vaughn et al, 2022), bien porque aportan claves para el aula (Calvo et al, 2021;Sampériz, Tabernero et al, 2020b;Sanjuán et al, 2022;Shimek, 2019;Tabernero et al, 2022) o bien porque contribuyen a seleccionar las obras estableciendo criterios de calidad (Goga et al, 2021;, pues las últimas investigaciones apuntan a que los docentes demandan directrices claras para ejercer adecuadamente la mediación lectora y literaria (Neira & Martín-Macho, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation